RANCANG BANGUN APLIKASI AUGMENTED REALITY MIFA BERBASIS ANDROID - mayana Evendy; Susi Wagiyati Putriningrum (Tekinfo: Jurnal Bidang Teknik Industri dan Teknik Informatika, 2020)
School is an institution for students where students is under the supervision of the teacher. The problems that arise are the way the teacher delivers learning material that sometimes seems boring without any activity, teachers who rarely bring students to the real world, less interactive and varied learning methods, lack of teaching aids for each lesson, especially in Mathematics and Natural Sciences lessons, and less attention to students abilities or talent. By using the interview method and direct observation of students and teachers who carry out this learning process. Augmented Reality based applications are technologies that expand our physical world by adding layers of digital information to it. Based on these observations, the authors succeeded in building the MIFA augmented reality application which aims to help the learning process to be more interactive, interesting, fun, and no longer monotonous. This MIFA augmented reality application implements augmented reality based technology, namely by applying it to 3D objects in learning materials. Where in use it can help students understand Mathematics and Natural Sciences lessons